2010
DOI: 10.1007/s11947-010-0491-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Native and Resistant Starches and Their Mixtures Using Near-Infrared Spectroscopy

Abstract: Resistant starches (RS) play important roles in our nutrition; therefore, the investigation of these starches is notably important. In our study, two native starches (maize and wheat) and two resistant starches (Hi-maize™260, high amylose maize starch as RS2 and Fibersym™70, phosphorylated wheat starch as RS4) were investigated as is and in their physical mixtures (samples containing 20%, 40%, 60% and 80% RS) using near-infrared (NIR) spectroscopy. The aim of our study was to examine the spectra of resistant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13] Starch-content models for maize or other cereal grains using NIR spectroscopy have been reported by several researchers. [14][15][16][17][18] Compared with NIR studies on corn-quality attributes, there have been relatively few studies on sorghum grain composition using NIR spectroscopy. For feed quality and seed viability, amylose, crude protein, amino acids, lipid and polyphenols contents, as well as gross calorific values, have been estimated using NIR spectroscopy and chemometrics.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Starch-content models for maize or other cereal grains using NIR spectroscopy have been reported by several researchers. [14][15][16][17][18] Compared with NIR studies on corn-quality attributes, there have been relatively few studies on sorghum grain composition using NIR spectroscopy. For feed quality and seed viability, amylose, crude protein, amino acids, lipid and polyphenols contents, as well as gross calorific values, have been estimated using NIR spectroscopy and chemometrics.…”
Section: Introductionmentioning
confidence: 99%
“…The main differences were observed in the NIR regions between 1100 and 1200 nm, related with C-H second overtones and between 2100 and 2300 nm with related with C-H, O-H stretching, C-C stretching bonds, and CONH 2 associated with several chemical constituents present in the whole barley matrix (e.g. starch) (Alencar-Figueredo et al, 2006;Delwiche et al, 1995;Gergely and Salgo, 2005;Hodsagi et al, 2012;Jacobsen et al, 2005;Workman and Weyer, 2008). Arngren et al (2011)) using hyper spectral NIR imaging of single kernels found that wavelengths between 1400 and 1550 nm can be associated with water activity related to barley germination as well as with the activity of starch and maltose.…”
Section: Tablementioning
confidence: 99%
“…Overall knowledge of the pasting properties of the sample can help to improve starch content in cereals and starchy foods as well as will allow understanding the biophysical and structural properties of the starch to be used in foods (e.g., bread, beer, whisky) and in industrial applications (e.g., polymer production) [ 13 ]. This can also provide with useful information about the specific application of the starch in the selection or screening of new genotypes or lines in breeding programs [ 6 , 14 ].…”
Section: Introductionmentioning
confidence: 99%